Land questions in modern Ireland - Campbell, Fergus J. M.; Varley, Tony (Book collections on Project MUSE., 2013)
Explores the nature and dynamics of Ireland's land questions during the 19th and 20th centuries, and also the ways in which the Irish land question has been written about by historians.